The Adipose Tissue Macrophages Central to Adaptive Thermoregulation - Rahman, Md. Shamim; Jun, Heejin (Frontiers in Immunology, 2022)
White fat stores excess energy, and thus its excessive expansion causes obesity. However, brown and beige fat, known as adaptive thermogenic fat, dissipates energy in the form of heat and offers a therapeutic potential to counteract obesity and metabolic disorders. The fat type-specific biological function is directed by its unique tissue microenvironment composed of immune cells, endothelial cells, pericytes and neuronal cells. Macrophages are major immune cells resident in adipose tissues and gained particular attention due to their accumulation in obesity as the primary source of inflammation. However, recent studies identified macrophages' unique role and regulation in thermogenic adipose tissues to regulate energy expenditure and systemic energy homeostasis. This review presents the current understanding of macrophages in thermogenic fat niches with an emphasis on discrete macrophage subpopulations central to adaptive thermoregulation.